Genotyping of hexaploid wheat varieties from different Russian regions - I. G. Adonina; I. N. Leonova; E. D. Badaeva; E. A. Salina (Вавиловский журнал генетики и селекции, 2016)
We used molecular-genetic and molecular-cytology approaches to characterize the genomes of 20 varieties of wheat created in different regions of Russia. A molecular-genetic analysis was performed using 29 SSR-markers covering the entire genome, and 41 ISBP-markers localized on chromosome 5B. Analysis of genetic similarity based on the results of molecular genotyping showed that the winter wheat varieties form a common cluster, regardless of the origin or area of cultivation. This is primarily due to the fact that the varieties originating from the European part of Russia were used to establish winter wheat varieties for West Siberia. Comparative analysis of individual dendrograms constructed using 1–2 markers per chromosome, and with the involvement of a larger number of 5B-chromosome markers allowed us to identify varieties with rearrangements of this chromosome and to assess genetic diversity. We found that winter wheat Vassa and spring wheat Chelyaba 75 were clustered closely together. This is an indirect confirmation of the use of winter wheat varieties in the breeding to improve the productive potential of spring wheat. Molecular-cytology analysis by C-banding and fluorescence in situ hybridization (FISH) revealed various chromosomal rearrangements in 8 of 20 cultivars studied, including translocations from S. cereale, Ae. speltoides and Th. intermedium. Thus, a combination of the two approaches allowed us to better characterize genomes of wheat varieties of various origin.